Double homozygous Cystic Fibrosis Transmembrane Regulator gene (CFTR) mutation: A case series and review of the literature - Hanaa Banjar; Wesam Alkassas; Firas Ghomraoui; Reem Ghomraoui; Nabil Moghrabi (Global Journal of Rare Diseases - Peertechz Publications, 2020)
Introduction: Double homozygous mutation with the presence of double mutations in each allele is a very rare phenomenon with only 2 reports that have described this phenomenon in the medical literature. Objective: To find the prevalence of double homozygous in our Cf population and to describe their mutations and review of the literature in this phenomenon. Methodology: A case series and a review of the literature from 1989-2020 for similar phenomenon. Results: A total of 396 patients (312 families) confirmed CF that were positive for the cystic fibrosis transmembrane conductance regulator (CFTR) variants from January 1998 to December 2018. A total of four families that constitute 4 patients were positive for double homozygous CFTR mutations in Trans position status. All parents were first-degree cousins. Their clinical pictures were of the severe type in relation to chest disease and failure to thrive. Family screening showed that 7 family members were carriers with double heterozygous mutations in Cis position. The Prevalence of double homozygous CFTR mutation in our study is 4/312 families or 1-2:100 families which is the highest that has been reported in the medical literature. Literature review showed only 2 cases of double homozygous were reported in 1995 and 2017.  Conclusion: Double homozygous CFTR mutations are common in the Saudi population due to consanguinity. Proper and extended genetic counseling is needed for the same family and their relatives to prevent similar conditions.